In situ Imaging of Tryptic Peptides by MALDI Imaging Mass Spectrometry using Fresh Frozen or Formalin-Fixed, Paraffin-Embedded Tissue - Angel, Peggi M. (Curr Protoc Protein Sci, 2018)
Tryptic peptide imaging is a primary workflow for matrix-assisted laser desorption/ ionization imaging mass spectrometry (MALDI IMS) and has led to new information reporting highly multiplexed protein localization. Technological advances within the last few years have produced robust tools for automated spraying of both matrix and enzymes. When combined with high mass resolution and high mass accuracy instrumentation studies now generally result in two dimensional mapping of well over 1,000 peptide peaks. This protocol describes sample preparation, spraying and application of enzymes and matrices, and MALDI FT-ICR instrumental considerations for two dimensional mapping of tryptic peptides from fresh frozen (FF) or formalin-fixed, paraffin-embedded (FFPE) tissue sections. Procedures for extraction of tryptic peptides from tissue sections for LC-MS/MS identification are also described.